(untitled) (Panacea Journal of Medical Sciences, 2016)
COPD is a disease state that causes lot of human suffering, is now recognized as a common disease in developing countries and is one of the fastest growing chronic cause of death. Pulmonary function tests are essential for the diagnosis and evaluation of the severity of COPD but other measures of functional status such as dyspnoea, exercise performance and health status are important components of COPD that cannot be measured by this method. The COPD assessment test (CAT) is a new eight-item specific questionnaire and is intended to provide a short, simple and self-administered test for evaluating symptoms, in assessing the impact of COPD on health status (Quality Of Life) .This study shows the usefulness of CAT score in our region. The clinical characteristics, Gold Severity and FEVI 1 % of present study were compared with earlier studies of different countries. Total 70 patients with COPD were studied from May 2014 to September 2014. Detail clinical history was obtained. Assessment of symptom severity was made based on the CAT questionnaire. They were subjected to pulmonary function test (pre and post bronchodilator therapy) and oxygen saturation measurement. Majority of the patients were Male 42(60%). Total 41(58.6%) patients were smokers of which 36 (87.8%) were males. 18(25.7%) patients had positive history of Chula exposure of which 17(94.4%) were females Mean age of patients was 60.3 years SD 9.9, Mean FEV1 62.33 SD 18.2, and SPO2 94.2 SD 2.27. Patients were classified into two groups. Group 1 of low symptoms having CAT Score <10 and high symptoms Group2of patients having CAT score >10. More than half of the patients 80% had a high CAT score of >10 of Group 2. Most of the patients were of moderate obstruction50%. Patients in whom Forced expiratory volume in 1 s percent (FEV1%) predicted was significantly decreased had a significantly increased the CAT score (t = 2.67 p= .009). Patients with severe stage of the disease (as GOLD criteria) had high CAT score i.e. have a positive correlation whereas CAT score and FEVI % had inverse co relation. The mean FEV1% predicted was similar to France where as high compared to Germany, Netherlands, Spain and USA and lower than Belgium. The CAT questionnaire proves to be a sensitive test in detecting COPD health status as a simple and reliable tool. By the help of CAT questionnaire the patients and clinician’s awareness of COPD would be improved to make an early diagnosis thus providing a useful and objective tool for early recognition and long-term clinical and therapeutic monitoring of COPD patients especially in the clinical settings where spirometry is not yet available.